Photoinduced oxidative cyclization of dithienylarenes - Barnabás Zsignár-Nagy; Viktória Kümmel; Tamás Gazdag; Péter J. Mayer; Zsófia Bokor; Tamás Holczbauer; Gábor London (Tetrahedron Green Chem)
A photoinduced electrocyclization followed by aerobic oxidation of 1,2-dithienylarene derivatives is described as a greener alternative to direct aryl-aryl couplings. The formation of the naphthodithiophene type products was monitored by UV–vis spectroscopy. Naphthodithiophenes with different structural features and electronic characters were accessed. Oxidative cyclization using the combination of BF3·Et2O and DDQ was a complementary approach to confirm the formation of the desired products. The method was also applicable to 2,3-dithienylbiphenylene having a backbone with antiaromatic character.